ANALISIS PENGGUNAAN DOUSHI SHINRAISURU, SHINYOUSURU DALAM KAMUS ELEKTRONIK TINJAUAN SEMANTIK - I Made Suardikayana R; I Wayan Wahyu Cipta Widiastika (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
In the Japanese language, there are word pairs that appear synonymous but differ in usage depending on context. This study examines two synonymous verbs, shinraisuru and shinyousuru both of which are commonly translated as “to trust” in Indonesian. The aim of the study is to identify differences in meaning and contextual usage between the two verbs. A contextual semantic approach was employed, based on Pateda’s (2010) theory which emphasizes that word meaning is heavily influenced by context, including situational, temporal, spatial, and linguistic factors. The data source is the digital Japanese dictionary Takoboto, which provides authentic definitions and usage examples. The method used is observation, by examining sentences containing each verb within the dictionary. The analysis reveals that shinraisuru tends to be used in emotional or interpersonal contexts, such as trust between friends or family members. In contrast, shinyousuru is more frequently found in formal or professional contexts, indicating trust based on evidence, reputation, or proven reliability. These findings demonstrate that although both verbs are classified as synonyms, there are significant semantic distinctions between them, shaped by the context in which they are used.